The role of management accounting in a turnaround strategy / Adibah Jamaluddin, Nurul Izwah Mohd Husin and Normah Omar - Jamaluddin, Adibah; Mohd Husin, Nurul Izwah; Omar, Normah (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA (UiTM) Shah Alam, 2018)
This paper investigated how management accounting (MA) was applied in a turnaround strategy to recover from a company’s fragile business position. A case study at a Malaysian company, Care, that went through a turnaround process was conducted to understand how the use of MA contributed to their turnaround process. While an economic downturn is claimed to be the major cause of poor organisational performance, Care was in a financial distress situation before the economic crisis. More importantly, Care successfully recovered their poor condition during the economic downturn with the use of MA techniques. This paper describes the way MA was utilised before, during and after the turnaround process. Prior to the economic crisis, MA was used merely to provide reports with no strategic focus. Failure to manage cost and understand the changes in the market compromised their performance. It is during the turnaround phase that MA information was used to understand the company’s current performance to devise a turnaround strategy, cost reduction and revenue generation. Concurrently, MA techniques which focused on quality was introduced. Consequently, better quality products at a lower production cost contributed towards improving their financial performance. More sophisticated MA techniques were introduced post turnaround period to sustain their performance. This paper contributes toward demonstrating how MA facilitates the turnaround process while undergoing an economic crises. Concurrently, it helps to minimise the gap between MA theory and practice by describing the application of MA in a turnaround strategy.